Strategic planning of national or regional systems of biosphere reserves: a methodology and case study from Costa Rica - Cifuentes, M.; MacFarland, C.; Morales, R. (Centro Agronómico Tropical de Investigación y Enseñanza, Turrialba (Costa Rica), 2014)
Ilus. Tab. 8 ref. Sum. (En)